2001
DOI: 10.1034/j.1600-0501.2001.012002115.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorbable versus nonabsorbable membranes and bone grafts in the treatment of ligature‐induced peri‐implantitis defects in dogs

Abstract: The purpose of this study was to clinically evaluate an absorbable collagen membrane (Bio-Gide) and a nonabsorbable polytetrafluoroethylene membrane (PTFE), associated or not with bone grafts, for the treatment of ligature-induced peri-implantitis defects in dogs. The bilateral mandibular premolars were removed from 5 2-year-old mongrel dogs. After 3 months of healing, 3 titanium implants were placed on each side of the mandible. Experimental peri-implantitis was induced after abutment connection. Ligatures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 10 publications
4
66
0
6
Order By: Relevance
“…Ligatures are typically removed after 2-3 mos, when approximately 30-50% of bone support is lost. Peri-implant bone defects are circumferential and wide, but rarely result in shallow craters (Lindhe et al, 1992;Grunder et al, 1993;Nociti et al, 2001a;Schwarz et al, 2007). The microflora associated with experimental peri-implantitis demonstrates many similarities to natural peri-implantitis lesions (Nociti et al, 2001b;Shibli et al, 2003).…”
Section: Ligature-induced Peri-implant Defectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ligatures are typically removed after 2-3 mos, when approximately 30-50% of bone support is lost. Peri-implant bone defects are circumferential and wide, but rarely result in shallow craters (Lindhe et al, 1992;Grunder et al, 1993;Nociti et al, 2001a;Schwarz et al, 2007). The microflora associated with experimental peri-implantitis demonstrates many similarities to natural peri-implantitis lesions (Nociti et al, 2001b;Shibli et al, 2003).…”
Section: Ligature-induced Peri-implant Defectsmentioning
confidence: 99%
“…In contrast, the microflora and the morphology are similar to the human situation, making this model suitable for studying the effects of NMF on the treatment of peri-implantitis. Consideration of biomaterials, biologics, and GBR techniques have been preferentially evaluated in these models (Nociti et al, 2001a;You et al, 2007). Potential endpoint measurements include percentage of vertical bone fill, height of new bone, and BIC (mm or %), as well as other parameters of osseointegration.…”
Section: Ligature-induced Peri-implant Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed that debridement alone as well as grafting alone had the same effect as did either membrane. 26 However,Hurzeler and coworkers reported in an invitro canine study that guided bone regeneration procedures resulted in the greatest amount of new bone formation, followed by bone grafts alone, and flap debridement. 27 In humans, Roos-Jans˚aker et al were able to show similar response to therapy i.e implants pocket reduction of 2.9-3.4mm and new bone fill of 1.4-1.5mm for peri-implantitis sites treated with either bone grafts alone or bone grafts in conjunction with resorbable collagen membrane.…”
Section: Surgical Treatment Of Perimentioning
confidence: 99%
“…Outro fator importante é o volume final de osso neoformado alcançado pela ROG utilizando membrana reabsorvível, que apresentou resultados semelhantes àqueles obtidos com membrana de PTFE-e (Carpio et al, 2000;Nociti et al, 2001).…”
Section: Biodegradação Da Membranaunclassified